TİCARİ İŞLETMENİN DEVRİNDE TASARRUF İŞLEMLERİNE İLİŞKİN ŞEKİL SORUNU - (:unkn) unknown (My University, 2012)
Eski Ticaret Kanununda ticari işletmenin devri hususunda bir düzenleme yoktu. Ticari işletmelerin devri Borçlar Kanununa göre yapılmaktaydı. Borçlar Kanununa göre devir sözleşmesi şekle tabi değildi. Fakat ticari işletmenin malvarlığı unsurları tek tek özel biçimde yapılması gerekliydi. Yeni Borçlar Kanunu da aynı sistemi öngörmüştür. Ancak Ticaret Kanununun 11. maddesi yeni bir düzenleme getirmiştir. Buna göre, ticari işletme yazılı bir sözleşmeyle bir bütün halinde devredilebilecektir. Bu sözleşme ticaret siciline tescil edilince hükümlerini doğuracaktır. Ticari işletmenin malvarlığı değerleri için tek tek devir işlemi yapılmayacaktır.

There was not an arrangement regarding the transf er of commercial enterp rises in the f ormer Turkish Commercial Code. The transf er of commercial enterp rises was done according to the f ormer Turkish Code of Obligation. A transf er contract f or the transf er of enterprise was not subj ect to any f orm. However, the individual elements of the business assets of the entity had to be transf erred in a certain f orm one by one. The new Turkish Code of Obligation accepts the same system. However, Article 11 of the new Turkish Commercial Code brought to a new arrangement. Accordingly, a commercial enterprise shall be transf erred as a whole by a written contract. The provisions of this agreement shall have eff ect and bear consequence when registered to the trade register. The values of asset of commercial enterprises shall not be transf erred one by one.
İsviçre Birleşme Kanunu (Fusionsgesetz: FusG) ve Alman Hukuku Perspektifinde
Keywords: İktisat; İşletme